Issues of knowledge, language , philosophy, and anthropology in Hayy Bin Yaqzan bay Ibn Tufail cermonial approach - Moumeni, Aissa (Journal of Human Sciences, 2021)
The objective of this article is to present the totality of knowledge that furnishes the story of Hayy bin Yaqzan by Ibn Tufail. A historical document related to a specific era that starts from a philosophical point of view. If the secular and perceptual trend is one of the linguistic trends that emerged after the established levels of linguistic analysis, then this contribution puts the mystical trend in Hayy bin Yaqzan by Ibn Tufayl into practice to keep up positively with what is issued from modern linguistic studies.